2014
DOI: 10.1063/1.4903893
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-free inverted organic photovoltaics using a mixture of silver nanoparticle ink formulations for solution-processed top electrodes

Abstract: We report an investigation of inkjet-printed silver (Ag) nanoparticle inks combined with a poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) formulation for solution-processed top electrodes in inverted organic photovoltaics (OPVs) employing the poly(3-hexylthiopehene):phenyl-C61-butyric acid methyl ester material system. We propose a suitable mixture of Ag nanoparticle inks to control the printability and electrical conductivity of the solution-processed top electrode. Based on the proposed solution-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…[151] In general, the utilization of barrier interfaces on the upper and lower surfaces of the activel ayer isolates the active layer, which prevents penetration of oxygen and humidity and ultimately reduces degradation of the active layer.M oreover, metal-oxide interfacial layers tend to create bonds with atmospheric oxygen, whicht hus protects the metal electrode from oxidation. [153] Metal electrodes that yield high stabilityh ave also been produced by using various printing techniques for devices with normal [154] and inverted [155] architecture, as well as for tandem OPVs. The photoactivation of these films leads to O 2 scavenging and opens new horizons for thin films, which trap oxygen upon exposure to light.…”
Section: Electrodes and Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…[151] In general, the utilization of barrier interfaces on the upper and lower surfaces of the activel ayer isolates the active layer, which prevents penetration of oxygen and humidity and ultimately reduces degradation of the active layer.M oreover, metal-oxide interfacial layers tend to create bonds with atmospheric oxygen, whicht hus protects the metal electrode from oxidation. [153] Metal electrodes that yield high stabilityh ave also been produced by using various printing techniques for devices with normal [154] and inverted [155] architecture, as well as for tandem OPVs. The photoactivation of these films leads to O 2 scavenging and opens new horizons for thin films, which trap oxygen upon exposure to light.…”
Section: Electrodes and Interfacesmentioning
confidence: 99%
“…The photoactivation of these films leads to O 2 scavenging and opens new horizons for thin films, which trap oxygen upon exposure to light. They compared hexagonal silver grids preparedb yu sing either rollto-roll inkjet or roll-to-roll flexographic printing with ar oll-toroll thermally imprinted grid that was filled with silver.T hey observed that the embedded grid and the flexographic grid performed equally well, but the flexographic technique allowed faster processing andl ower silver use, and the embedded grid presented higher optical transparency and conductivity.I nkjet printing hasa lso been used [155] to produce solutionprocessed top electrodes for inverted P3HT:PCBM OPVs with ap owerc onversion efficiency in the vicinity of 3%.Amixture of Ag nanoparticle inks was developed in this case to control the printability and electrical conductivity of the electrodes. [152] At hin-film adhesion technique by using postdepositiona nnealing can be applied to flexible OPVs to increase adhesion between layers.…”
Section: Electrodes and Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Inkjet printing has been used for the deposition of all the layers of an OPV stack and recently some works have demonstrated fully IJP OPV. [7][8][9][10][11] Remarkably, inkjet printing has been widely used in the fabrication of metal grid designs as a substitution of the rigid and expensive ITO transparent conductor. [12][13][14][15] Nowadays, silver nanoparticle-based inks are dominant in the field and several efficient ITO-free OPVs with IJP silver grids have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Inkjet‐printing can also be transferred to a roll‐to‐roll (R2R) process, thereby accessing both a productivity of up to 6 m 2 min −1 and also small feature sizes (30–50 µm line/10 µm space) and a wide variety of shapes . Inkjet printing has been utilized in order to fabricate every component of an organic optoelectronic device, including the active layer materials and the metal top and transparent bottom electrodes . However, only very few devices have claimed to be wholly inkjet‐printed, paving the way for fully solution‐processed devices to become more widespread.…”
Section: The Printed Transparent Conductive Electrode In Organic Elecmentioning
confidence: 98%